Hindu equilibrium - "Lal, Deepak" (Oxford, 1989)
India is an emerging giant. This book explains its long economic stagnation and recent rise by examining its social, political and historical evolution in long term perspective. It explains how its distinct social system based on caste arose and why it still is of importance in its political and social arrangements, despite India's recent move from the plan to market.
Keywords: Labour supply-India